Characterization of a Continuous Beam Cold Atom Ramsey Interferometer - Michael P. Manicchia; Jeffrey G. Lee; Frank A. Narducci (Atoms, 2023)
The use of atom interferometers in inertial systems holds the promise of improvement of several orders of magnitude in sensitivity over sensors using current technology such as micro-electro-mechanical (MEMS) devices or ring laser gyroscopes (RLGs). This paper describes the construction and characterization of an atomic interferometry system for eventual use in a dual-atom-beam accelerometer/gyroscope sensor. In contrast with current state-of-the-art atomic sensors which use pulsed cold atom sources and pulsed laser beams, the investigated apparatus relies purely on continuous atomic and laser beams. These differences can result in a sensor with reduced complexity, a smaller physical footprint, and reduced power consumption. However, these differences also introduce challenges resulting from laser and atomic beam divergences and from velocity averaging due to both longitudinal and transverse velocity spreads. In this work, we characterize our rubidium-based atom beam system and show that Ramsey-style interference can still be observed. The implications for future research are also outlined and discussed.